An automatic EMI filter design and optimization for photovoltaic inverter - BEGGAT, F.; MILOUDI, K.; BOUCHAFAA, F. (University of Eloued جامعة الوادي, 2018)
Electromagnetic interference (EMI) issue has become one of the extremely important problems to be solved in the photovoltaic (PV) inverter system. It is well known that the static converters used in PV system are major sources of conducted disturbances which are the common mode and differential mode. Often, the solution used to reduce conducted emissions consists to use the EMI filters. In this paper, a complete computer aided procedure based on a co-simulation Matlab and LT-Spice. A Database representing the parasitic elements of the passive component, this last one allowed feed the program of design of the filter under Matlab. Finally, the final phase allowed to validate the filter performance with a temporal solver or / and frequency under LT-Spice. Simulation and experimental results give a firm support to the proposed method.
International Symposium on Mechatronics and Renewable Energies El-Oued 10- 11 December 2018
Keywords: Electromagnetic interference, automatic design, EMI filter, PV inverter, parasitic elements